An iPTH based protocol for the prevention and treatment of symptomatic hypocalcemia after thyroidectomy - Carter, Yvette (2013)
BACKGROUND: Symptomatic hypocalcemia after thyroidectomy is a barrier to same day surgery, and the cause of ER visits. A standard protocol of calcium and vitamin D supplementation, dependent on intact parathyroid hormone (iPTH) levels, can address this issue. How effective is it? When does it fail? METHODS: We performed a retrospective review of the prospective Thyroid Database from January 2006 to December 2010. 620 patients underwent completion (CT) or total thyroidectomy (TT), and followed our post-operative protocol of calcium carbonate administration for iPTH levels ≥10pg/ml and calcium carbonate and 0.25μg calcitriol BID for iPTH <10pg/ml. Calcium and iPTH values, pathology and medication, were compared to evaluate protocol efficacy. A p value <0.05 was considered statistically significant. RESULTS: Using the protocol, sixty-one (10.2%) patients were chemically hypocalcemic but never developed symptoms and twenty-four (3.9%) patients developed breakthrough symptomatic hypocalcemia. The symptomatic (SX) and asymptomatic (ASX) groups were similar with regard to gender, cancer diagnosis, and pre-operative calcium and iPTH. The symptomatic group was significantly younger (39.6 ± 2.8 vs. 49 ± 0.6 years, p=0.01), with lower post-operative iPTH levels. 33% (n=8) of SX patients had an iPTH ≤5 pg/ml vs. only 6% (n=37) of ASX patients. While the majority of patients with a PTH <5 pg/ml were asymptomatic, 62.5% (n=5) of SX patients with iPTH levels ≤5 pg/ml, required an increased in calcitriol dose to achieve both biochemical correction and symptom relief. CONCLUSION: Prophylactic calcium and vitamin D supplementation based on post-operative iPTH levels can minimize symptomatic hypocalcemia after thyroidectomy. An iPTH ≤ 5pg/ml may warrant higher initial doses of calcitriol in order to prevent symptoms.